2019
DOI: 10.3390/medicina55050160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cariprazine, Aripiprazole, and Olanzapine on Mouse Fibroblast Culture: Changes in Adiponectin Contents in Supernatants, Triglyceride Accumulation, and Peroxisome Proliferator-Activated Receptor-γ Expression

Abstract: Background and Objectives: The use of the dopamine-partial agonist subclass (also termed dopamine stabilizers) of atypical antipsychotics for the treatment of negative schizophrenia symptoms and some mood disorders has increased recently. Similar to other second-generation antipsychotics (SGAs), aripiprazole (ARI) and cariprazine (CAR) also influence food intake, but the peripheral effects of these drugs on adipose–tissue homeostasis, including adipokine secretion as well as lipo- and adipogenesis, are not ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In this view, the reduction of the rates of lipolysis in response to the β-adrenergic agonist isoprenaline was consistently reported in both rats [10] and cultured preadipocytes [14] treated with olanzapine. Moreover, atypical antipsychotics have been described to alter other biological functions of adipocytes, not only related with the management of triglyceride storage/breakdown (lipogenesis and lipolysis) [11,15], but also related to insulin sensitivity and inflammation, such as adipokine secretion [12,14], therefore favoring the onset of insulin resistance. Nevertheless, no functional studies of the lipolytic responses to neuropsychiatric drugs have been performed in human mature adipocytes to date, whereas it has been documented that several antipsychotic drugs alter in vitro gene expression in human mesenchymal stem cells differentiated into adipocytes [2,[16][17][18].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In this view, the reduction of the rates of lipolysis in response to the β-adrenergic agonist isoprenaline was consistently reported in both rats [10] and cultured preadipocytes [14] treated with olanzapine. Moreover, atypical antipsychotics have been described to alter other biological functions of adipocytes, not only related with the management of triglyceride storage/breakdown (lipogenesis and lipolysis) [11,15], but also related to insulin sensitivity and inflammation, such as adipokine secretion [12,14], therefore favoring the onset of insulin resistance. Nevertheless, no functional studies of the lipolytic responses to neuropsychiatric drugs have been performed in human mature adipocytes to date, whereas it has been documented that several antipsychotic drugs alter in vitro gene expression in human mesenchymal stem cells differentiated into adipocytes [2,[16][17][18].…”
Section: Introductionmentioning
confidence: 74%
“…Previous investigations have been performed by measuring adipocyte biological functions and determining the regulations of key genes involved in metabolic pathways, either in adipocytes from treated animal models [10], or after short-or long-term incubation of cultured adipose cells with psychoactive molecules. To briefly mention examples of such different approaches, it is worth mentioning that the decreased lipolytic effect of isoprenaline and down-regulated hormone-sensitive lipase gene (Hsl) were found in adipocytes from olanzapine-treated rats [10], whereas increased lipid accumulation and adipogenic gene upregulation were observed in cultured adipocytes treated with olanzapine [2,[11][12][13][14]. In this view, the reduction of the rates of lipolysis in response to the β-adrenergic agonist isoprenaline was consistently reported in both rats [10] and cultured preadipocytes [14] treated with olanzapine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the effect of aripiprazole on adiponectin are inconsistent. An in-vitro study reported that aripiprazole increases blood adiponectin levels in the supernatants on mouse fibroblast cultures ( 120 ). Another in-vitro study revealed that aripiprazole does not change the mRNA expression of ADIPOQ gene on human subcutaneous adipose tissue ( 121 ).…”
Section: Effects Of Antipsychotics On Adiponectinmentioning
confidence: 99%
“…Concerning the dyslipidemia, the role of PPARs have long been hypothesized [7]. In order to assess the involvement of AT-related mechanisms, we previously measured under in vitro conditions the expression of PPAR-γ after SGA administration during adipogenesis [37]. Although the protein expression (at protein level-measured by Western blot) was not changed under in vitro conditions in the mentioned experience, in 3T3-L1 cell line others found an increase in PPAR-γ expression by Ola [17].…”
Section: Effect On Body Weightmentioning
confidence: 99%